PENGEMBANGAN DESAIN SLING BAG DENGAN MATERIAL KOMBINASI KAIN DAN LAMINASI BAMBU - Mahendra, Marcellino Aditya (Indonesian Society of Applied Science, 2025)
The sling bag, initially a mere portable storage container, has evolved into an essential fashion accessory in modern urban life. Its ergonomic design allows users to move freely while carrying essential items. Sling bags are popular among students and professionals due to their practicality. Although used by both men and women, sling bags are more often associated with women due to their diverse designs, specialized functionalities, and role in women's fashion styles. The popularity of sling bags continues to rise, driving innovation in aesthetics and material sustainability. In the context of global sustainability, bamboo emerges as a promising eco-friendly alternative. The lightweight, strong, and natural aesthetic properties of bamboo, combined with lamination technology, enable the development of innovative and sustainable fashion products. This research aims to develop an innovative sling bag design by combining fabric and laminated bamboo, focusing on functionality, aesthetics, and sustainability. The application of this material combination technique is expected to produce unique and robust products, contributing to the development of sustainable fashion by utilizing the potential of bamboo.